Process evolution in cell and gene therapy from discovery to commercialization. (18th May 2021) - Csaszar, Elizabeth; Mills, Sara; Zandstra, Peter W.
Abstract: The field of cell and gene therapy (CGT) is maturing at a rapid rate. Manufacturing remains a major challenge and manufacturing failures and limitations are a notable source of CGT products not meeting specification or being held back from regulatory approvals. To ensure that products remain compliant and competitive throughout their lifecycle, CGT process development requires both ongoing advancement of fit‐for‐purpose technologies to allow for and support well‐designed development studies, and a methodology that enables these studies to occur effectively during focused product development campaigns. We describe a framework for ongoing innovation in CGT process development, manufacturing, and clinical testing, based on the quality by design (QbD) approach. We propose use of the concepts of process discovery, process characterization, and process development in an iterative way to refine the design space as a product matures. This strategy is enabled by the early implementation of broad and robust analytics, and a modular approach to accelerate optimization. With these strategies, CGT developers can prospectively plan for comparability studies and develop in a stage‐appropriate manner, to allow for ongoing innovation and improvements from discovery through to commercialization.